2021
DOI: 10.1111/jog.14874
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy via transvaginal natural orifice transluminal endoscopic surgery versus single‐port laparoscopy: Comparison of early outcomes

Abstract: Aim: The study objective was to compare intraoperative and early postoperative outcomes among patients who underwent hysterectomy via transvaginal natural orifice transluminal endoscopic surgery (and singleport lararoscopy for presumed benign gynecologic disorders). Methods: We retrospectively reviewed 40 patients who underwent single-port laparoscopic hysterectomy and 20 patients who underwent hysterectomy via natural orifice transluminal endoscopic surgery. Patients' age, body mass index, history of previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…It was also found that patients who underwent vNOTES experienced less postoperative pain than those who underwent SPA laparoscopic surgery, and the total operative time of vNOTES was shorter than that of SPA laparoscopic surgery. To the best of our knowledge, the present study is the third to compare the surgical outcomes of vNOTES and SPA hysterectomy [ 12 , 13 ]. Both previous studies have demonstrated comparable surgical outcomes of vNOTES to those of SPA laparoscopic surgery, but those studies were conducted retrospectively whereas the present study was designed as a prospective cohort study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that patients who underwent vNOTES experienced less postoperative pain than those who underwent SPA laparoscopic surgery, and the total operative time of vNOTES was shorter than that of SPA laparoscopic surgery. To the best of our knowledge, the present study is the third to compare the surgical outcomes of vNOTES and SPA hysterectomy [ 12 , 13 ]. Both previous studies have demonstrated comparable surgical outcomes of vNOTES to those of SPA laparoscopic surgery, but those studies were conducted retrospectively whereas the present study was designed as a prospective cohort study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a comparative investigation of the surgical outcomes of vNOTES and SPA laparoscopic surgery has not been conducted to date. To the best of our knowledge, only two studies have compared the operative outcomes of vNOTES and SPA laparoscopic surgery [ 12 , 13 ]. The present study aimed to compare the two surgical methods.…”
Section: Introductionmentioning
confidence: 99%
“…32 However, experienced surgeons can minimize the risk of complications compared with other surgical routes. 33 Although hysterectomy through vaginal natural orifice transluminal endoscopic surgery (vNOTES) has the advantage of no abdominal wall incisions compared with single-port hysterectomy, 34 factors such as increased technical difficulty and limited mobility of the uterus can limit its practicality. Conversely, laparoscopic hysterectomy offers several advantages over robotic-assisted hysterectomy, including lower cost, shorter surgical time, fewer ports needed, and similar outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with conventional transvaginal surgery, the surgical field of SvNOTES can be clearly visualized using an endoscopic camera; any pathology beyond the reach of the operator can be easily managed with the assistance of laparoscopic instruments ( 18 , 19 ). More importantly, it has the advantage of the absence of abdominal scarring ( 20 ).…”
Section: Discussionmentioning
confidence: 99%